2018
DOI: 10.1007/s40037-017-0392-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive load predicts point-of-care ultrasound simulator performance

Abstract: Introduction The ability to maintain good performance with low cognitive load is an important marker of expertise. Incorporating cognitive load measurements in the context of simulation training may help to inform judgements of competence. This exploratory study investigated relationships between demographic markers of expertise, cognitive load measures, and simulator performance in the context of point-of-care ultrasonography. Methods Twenty-nine medical trainees and clinicians at the University of Toronto wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 39 publications
(56 reference statements)
4
20
1
Order By: Relevance
“…It has been utilised to generate instructional principles for designing anatomical multimedia and generalisable design guidelines for medical education . Further, CLT has served as a useful lens when analysing medical training methods …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been utilised to generate instructional principles for designing anatomical multimedia and generalisable design guidelines for medical education . Further, CLT has served as a useful lens when analysing medical training methods …”
Section: Introductionmentioning
confidence: 99%
“…14 Further, CLT has served as a useful lens when analysing medical training methods. [15][16][17][18][19] Technological solutions have also been suggested as a tool for improving anatomical education, including mobile technology 20 or three-dimensional (3-D) display technology. 21 This article focuses on 3-D display technology, using a categorisation suggested by Geng.…”
mentioning
confidence: 99%
“…Regarding the test–retest reliability, the extraneous CL was the least stable factor among the three identified factors in the Chinese version MDT‐CL. The possible reason might include the following: (a) there are only three items included in the extraneous CL and Leppink et al (Leppink et al, ) indicated that the stability of a scale or subscale can be affected when there are only few items within a scale or subscale and (b) extraneous CL may vary when the participant's emotions (Pawar et al, ) or the physical environment (Aldekhyl, Cavalcanti, & Naismith, ) is subject to change. Future studies are needed to conduct equivalence reliability for testing the stability of the extraneous CL (Park et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between extraneous CL and germane CL (r = 0.003) in our study is different than the original study (r = −0.19). If a nursing care activity is presented to a nurse in a simple or familiar way, and there is a lower extraneous CL, it seems that the nurse may devote more cog- (Pawar et al, 2018) or the physical environment (Aldekhyl, Cavalcanti, & Naismith, 2018) is subject to change.…”
Section: Discussionmentioning
confidence: 99%
“…The paper ‘Cognitive load predicts point-of-care ultrasound simulator performance’ by Aldekhyl, Cavalcanti, and Naismith, in this issue of Perspectives on Medical Education [ 1 ], is an important paper that adds to work on cognitive load theory and medical education [ 2 4 ]. The implications of the findings of this paper extend substantially beyond the confines of medical practice that is the focus of the work.…”
mentioning
confidence: 99%